2019
DOI: 10.1111/eve.13080
|View full text |Cite
|
Sign up to set email alerts
|

Pine branch of Araucaria angustifolia in horse bronchi: A series of four cases

Abstract: SummaryHorses at pasture are susceptible to the aspiration of foreign bodies. In Curitiba, southern Brazil, four horses of different breeds and ages were examined with regards to a persistent cough that lasted for several months, fetid breath, and no fever. The animals were referred for bronchoscopic examination performed under sedation and tracheobronchial topical anaesthesia. Bronchoscopies in all four horses revealed a pine branch of the species Araucaria angustifolia, native to southern Brazil, in the lume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…In our study, dyspnea, hemoptysis, and fever were observed, similarly to previous case descriptions of FBs inhalation in horses (BARUSSI et al, 2020;FERRUCCI et al, 2003;MAIR, 2006;URQUHART et al, 1981). However, these descriptions reported chronic cough, which was not observed in our case, possibly due to the rapid progression of clinical signs.…”
supporting
confidence: 92%
See 4 more Smart Citations
“…In our study, dyspnea, hemoptysis, and fever were observed, similarly to previous case descriptions of FBs inhalation in horses (BARUSSI et al, 2020;FERRUCCI et al, 2003;MAIR, 2006;URQUHART et al, 1981). However, these descriptions reported chronic cough, which was not observed in our case, possibly due to the rapid progression of clinical signs.…”
supporting
confidence: 92%
“…FBs in the respiratory tract may be diagnosed by endoscopy and the removal is commonly successful (BARUSSI et al, 2020). Findings of post-mortem examinations carried out in fatal cases of FB inhalation in horses include large amounts of free serohemorrhagic fluid in the thoracic cavity, fibrinous pneumonia, with multifocal adhesions between the parietal and visceral pleura (BODECEK et al, 2011).…”
Section: Molossi Et Almentioning
confidence: 99%
See 3 more Smart Citations